Penggunaan TID-ID untuk Menonton di Sinema XXI pada Masa Pandemi Covid-19 - Meylani Tuti; Shilviana Jihan (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
The purpose of the study was to analyze the impact of the influence of e-commerce and brand image on customer satisfaction through purchase decisions. The population in this study are customer, namely film viewers at Cinema XXI North Jakarta and South Bekasi who use TIX ID more than twice. The sampling technique used purposive sampling by distributing google form on 275 viewers who bought tickets using TIX-ID. Data have been tested on the validity and reliability. The method data analysis is by using descriptive and quantitative. The quantitative analysis is conducted by using Structural Equation Modeling (SEM). The result of this study indicates that e-commerce influences purchase decisions by t-value of 2.15, brand image influences purchase decisions by t-value of 5.63, e-commerce influences customer satisfaction by the t-value of 1.97, brand image influences customer satisfaction by the t-value of 2.56, purchase decisions influence customer satisfaction by the t-value of 3.07. Additionally, there is no significant indirect effect between e-commerce on customer satisfaction through purchase decisions by the t-value of 1.72, there is an indirect effect between brand image on customer satisfaction through purchase decisions by the t-value of 2.72.